Stridor in pediatrics is not only laryngomalacia - Bredun, Sergii; Adamczyk, Paulina; Żychowski, Piotr; Nowak, Nel; Szydłowski, Jarosław (Journal of Medical Science, 2024)
Introduction. Stridor in newborns and infants is a common manifestation of airway obstruction that can be caused by both benign and severe pathologies.Aim. This literature review examines the diseases that can present with stridor in children after birth, with the aim of better understanding their etiology, clinical course, and treatment.Material and methods. The literature reviewed included published studies, reports, guidelines, and consensus statements on pediatric laryngeal pathologies associated with stridor.Results. Laryngomalacia is the leading cause of stridor (up to 75% of cases) with a mostly mild course that requires only observation. However, stridor may also indicate other, often more serious laryngeal pathologies, such as vocal cord paralysis, subglottic stenosis, laryngeal cleft, and subglottic haemangioma, usually requiring surgical intervention.Conclusions. Stridor is not a specific symptom of only laryngomalacia. Laryngeal pathologies manifested as stridor can have different etiology and, as a result, require a fundamentally different approach to treatment.
Keywords: stridor; laryngomalacia; vocal cord paralysis; subglottic stenosis; laryngeal clefts; subglottic hemangioma